2007
DOI: 10.1159/000098656
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy with an Aluminum Hydroxide-Adsorbed <i>Juniperus ashei</i> Foreign Pollen Extract in Seasonal Indigenous Cypress Pollen Rhinoconjunctivitis

Abstract: Background:The efficacy of standardized Juniperus ashei extract was assessed in patients with allergic rhinoconjunctivitis due to European cypress pollens. Methods:Forty adults with European cypress-allergic rhinoconjunctivitis were randomized to receive immunotherapy or a matched placebo. Specific immunotherapy was performed with a standardized, aluminum hydroxide-adsorbed J. ashei extract with a potency of 100 IR (arbitrary index of reactivity) containing 54 µg of Jun a 1/ml (Alustal, Stallergenes, France). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Charpin et al . (2007) found mean Juniperus‐specific IgG4 levels in the treatment group to be increased from baseline (251.5 g/L) in the first (5771.7 g/L, p = 0.00001) and second pollen seasons (11,108.4 g/L, p = 0.0001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Charpin et al . (2007) found mean Juniperus‐specific IgG4 levels in the treatment group to be increased from baseline (251.5 g/L) in the first (5771.7 g/L, p = 0.00001) and second pollen seasons (11,108.4 g/L, p = 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…Charpin et al . (2007) published a study of 40 patients comparing SCIT using an aluminum adsorbed Juniperus ashei extract in patients with allergic rhinoconjunctivitis due to European cypress pollens with placebo to investigate the concept of SCIT treatment with major allergen challenge.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the structural homology of their major allergens, genuine sensitization to either Cupressus arizonica and/or C. sempervirens , both prevalent in the Mediterranean basin, may be confirmed by this single assay [39]. In this case, the high level of cross-antigenicity between members of the Cupressaceae family may justify therapeutic administration of a single representative pollen extract, even if it is not the same as the originally sensitizing species [40]. …”
Section: Markers Of Genuine Sensitization To Major Pollen Sourcesmentioning
confidence: 99%
“…Ocular symptoms are rarely reported separately. Charpin et al conducted a double blind placebo control (DBPC) trial in ARC patients and reported a 41% reduction in AC symptoms (p = 0.02) [51]. One of the very few randomized trials of SCIT in AC concluded with statistical significance that SCIT (62% pollen, 19% HDM) was more effective than local pharmacotherapy in reducing the AC symptoms [52].…”
Section: Scit For Allergic Conjunctivitismentioning
confidence: 99%